Electron diffraction from nanovolumes of amorphous material using coherent convergent illumination. - McBride, W; Cockayne, D; Nguyen-Manh, D (2003)
Using a conventional transmission electron microscope that incorporates a field emission gun it is possible to focus an electron beam to form a small probe (<1nm full-width at half-maximum). Such a probe can then be used to perform high spatial resolution diffraction experiments. The high spatial resolution allows technologically interesting amorphous volumes, such as those found in glassy intergranular phases or in semiconductor implantations, to be investigated directly. In order to achieve the probe characteristics necessary to investigate nanovolumes of material the probe must be highly convergent which results in it being highly coherent. In this paper we examine the effect of coherent convergent illumination on electron diffraction data taken from nanovolumes of amorphous material. It is shown that, for amorphous volumes as small as 1.2nm in diameter, the additional interference effects induced in the diffraction data by the use of coherent convergent illumination are largely suppressed by the lack of order in amorphous materials. This allows the use of deconvolution techniques, developed for the correction of broadening of the diffraction pattern in the case of incoherent illumination, and the subsequent application of reduced density function (G(r)) analysis, to also be used for coherent illumination.